Questioning Environmental Rights: The Role of NGOs in Horizontal Environmental Disputes in South Africa and Indonesia - Fersanda Batrysia Alaina (Universitas Airlangga, 2025)
Significant gaps in environmental protection continue to arise from the combined pressures of climate change, human rights challenges, and institutional weaknesses. This paper compares the distinct roles of non-governmental organizations (NGOs) in addressing environmental and climate change disputes in Indonesia and South Africa. Employing a comparative legal analysis of each country’s horizontal human rights framework and relevant case studies, the study identifies notable divergences in NGO strategies. In South Africa, the direct horizontal application of rights enables NGOs to pursue strategic litigation that strengthens corporate accountability. By contrast, Indonesia’s indirect horizontal application compels NGOs to rely more heavily on public advocacy, mobilization, and judicial interpretation to confront both state and private actors. The paper concludes that NGOs play a supplementary role by providing expertise and resources to enhance policy and enforcement. It argues that adopting a direct horizontal application, as in South Africa, could strengthen Indonesia’s capacity to hold multinational corporations directly accountable for environmental harm.